ETIKA BERBAHASA DALAM PELAYANAN PUBLIK - Suhartono Suhartono; Enny Dwi Lestariningsih (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2016)
Services in the bureaucracy are still complained by the public. It means that the service within the bureaucracy still needs to be improved. Society calls for excellent service. Excellent service is a service to meet the expectations and needs of the community/customer. Bureaucracy in serving the public needs to consider the principles of the excellent service, which is the principle (1) ability, (2) attitude, (3) appearance, (4) attention, (5) action, and (6) accounttability, (7)